Solidary Social and Feminist Economies: Heterodox Responses to the Crisis of Reproduction in Latin America - Quiroga Díaz, Natalia (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2009)
In Latin America, the crisis of reproduction has put to question the way in which the economy has been understood. This, in turn, has spurred a convergence of criticism that has repositioned human and planetary life at the centre of the agenda. This article examines the convergence from both a feminist and a socio-economic perspective. Both perspectives believe in the need to conceptually reformulate the economy, the need to redimension the reproductive sphere, and the recognition of the importance of the cultural and symbolic dimension. Both have critical theoretical foundations that reveal the patriarchal system and the dominance of the utilitarian rationale that manifests itself in the conception of the homo economicus and the total market.